Analisis Pengaruh Saluran Distribusi Untuk Peningkatan Volume Penjualan Domba Pada Taznika Farm - Tabina Syafira; Siti Nur Ruqoyah; Deby Pazrin; M Ifran Z (Jurnal Bisnis Kreatif dan Inovatif, 2024)
This study aims to analyze the influence of distribution channels on the sales volume of sheep at Taznika Farm. The research method used was a survey of sheep farmers. The results showed that the distribution channel has a significant effect on sheep sales volume. Direct distribution from producer to end consumer is more effective in increasing sales volume compared to indirect channels. Developing and optimizing both direct and indirect distribution channels can expand marketing reach and increase sheep sales at Taznika Farm. Further research is needed to identify other factors affecting sales volume to inform a more comprehensive marketing strategy.